Leadership Agility, Entrepreneurial Experience, Organizational Culture, and Social Capital in Enhancing Sustainability of Agricultural SMEs: A Systematic Literature Review - Sudarma, Ade; Nugroho, Arissetyanto; Derriawan, Derriawan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2026)
The sustainability of agricultural small and medium-sized enterprises (SMEs) has become a critical issue amid increasing economic uncertainty, climate change, and global market dynamics. Although prior studies have extensively examined the determinants of SME sustainability, limited attention has been given to the integrated role of internal organizational factors particularly leadership agility, entrepreneurial experience, and organizational culture along with the mediating function of social capital, especially in the agricultural context. This study aims to identify, map, and synthesize empirical findings on how internal organizational capabilities influence the sustainability of agricultural SMEs through a Systematic Literature Review (SLR). The review follows PRISMA guidelines and analyzes articles retrieved from Scopus, Web of Science, and Google Scholar published between 2014 and 2024. A total of 36 peer-reviewed articles were selected and examined using thematic and conceptual analysis. The findings reveal that leadership agility, entrepreneurial experience, and organizational culture consistently contribute to SME sustainability, both directly and indirectly through the strengthening of social capital. Social capital plays a crucial mediating role by enhancing access to resources, networks, and collective support, thereby reinforcing business resilience. This study proposes an integrative conceptual model that links internal organizational capabilities and social capital in explaining the sustainability of agricultural SMEs. The findings offer theoretical contributions by integrating the Resource-Based View and social capital theory, as well as practical implications for designing leadership development and networking-based policies to support sustainable agricultural SMEs.